Decision of the Constitutional Court of the Republic of Indonesia regarding Criminal Procedure Law in Criminal Law Enforcement in the City of Kediri - Nurhayati, Siti; Rizal, Moch. Choirul; Dermawan, Rizki (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2024)
Several decisions of the MK formulated new arrangements regarding criminal procedural law in Indonesia. However, the legislature has yet to follow up. Therefore, this study focuses on describing and providing prescriptions regarding MK decisions which were followed up by criminal law enforcement officers in Kediri City along with the embodiment of the principle of legal certainty. Legal research (which is certainly normative) uses statutes, case and conceptual approaches. This research was conducted in the City of Kediri by collecting primary, secondary, and non-legal legal materials using library research, interviews, and focus group discussion techniques. Analysis in research is prescriptive to find the truth of coherence. As a result, first, the decisions of the MK that changed several articles in the criminal procedural law in Indonesia have been followed up by criminal law enforcement officials in the City of Kediri through the centralized policies of each institution. Second, several policies following up on the MK decision have guaranteed the realization of the principle of legal certainty, except for the issuance of a circular letter from the MA which confirms that a request for review is only 1 (one) time. However, these follow-up actions are not actually within the authority of each institution and are still partial in nature, giving rise to relatively one-sided interpretations and disparities in the handling of criminal cases.